PELAKSANAAN UPAH KERJA LEMBUR PADA PT ASIA FORESTAMA RAYA BERDASARKAN KEPUTUSAN MENTERI TENAGA KERJA DAN TRANSMIGRASI NOMOR Kep.102/Men/VI/2004 - Shandy Utama, Andrew; Kamilah, Faizah (Komunitas Manajemen Kompetitif, 2019)
Pursuant to Article 78 of Law No. 13/2003 it is stated that companies which employ workers exceeding work hours as stipulated in Article 77 of the law are required to pay overtime wages. This research aims to explain the implementation of overtime wages at PT Asia Forestama Raya based on the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia No. Kep.102/Men/VI/2004 regarding Overtime and Overtime Wages. The method used in this research is socio-legal research. The results of the research explained that PT Asia Forestama Raya did not pay overtime wages to its factory workers who had worked more than hours worked as stipulated in Law No. 13/2003. The obstacle is because the company's financial condition is currently in an unstable condition and there is an agreement between the company management and factory workers that PT Asia Forestama Raya is unable to pay overtime wages to its workers. The legal settlement if PT Asia Forestama Raya does not pay overtime wages to its workers who have worked more than working hours, then the company may be subject to criminal sanctions under Article 187 of Law No. 13/2003.